Cannabinoid use in psychotic patients impacts inflammatory levels and their association with psychosis severity. (November 2020) - Gibson, Claire L.; Bassir Nia, Anahita; Spriggs, Sharron A.; DeFrancisco, Daniel; Swift, Amy; Perkel, Charles; Zhong, Xiaobo; Mazumdar, Madhu; Fernandez, Nicolas; Patel, Manishkumar; Kim-Schulze, Seunghee; Hurd, Yasmin L.
Highlights: Participants were patients admitted to an inpatient psychiatric unit for acute psychosis. Inflammatory markers (IFN-γ, IL-12, IL-6, IL-2, IL-1β, TNF-α, IL-10, IL-21, IL-8, CRP, and sIL-2Ra) were compared between cannabinoid-positive and negative participants. Severity of psychosis (measured with the positive and negative syndrome Scale, PANSS) was similar between cannabinoid-positive and cannabinoid-negative participants. Cannabinoid-positive participants had comparatively lower levels of IFN-γ, though results did not survive covariate or multiple comparison adjustment, and must be interpreted with caution. IL-6 levels of cannabinoid-positive participants significantly negatively correlated with positive and negative PANSS symptom subscales. Abstract: Inflammatory abnormalities are well-documented in individuals with chronic psychotic disorders. Particular attention has focused on interleukin-6 (IL-6) and its correlation with psychotic symptom severity. Cannabis use is associated with an increased risk of psychosis and also has immunomodulating properties. It has been hypothesized that inflammatory disturbances are a common underlying pathology between cannabis use and psychosis. We measured inflammatory markers in individuals admitted to a psychiatric unit with acute psychosis who had toxicology positive for natural and/or synthetic cannabinoids ( n  = 59) compared to patients with negative cannabinoid toxicology ( n  = 60). Psychosis severity was assessed using the Positive and Negative Syndrome Scale (PANSS). While PANSS scores were similar between groups, cannabinoid-positive participants were more likely to receive pro re nata (PRN or as-needed) medications for agitation in the psychiatric emergency room, particularly synthetic cannabinoid-positive participants. In unadjusted models, cannabinoid-positive participants had lower interferon-γ (IFN-γ) levels ( p  = 0.046), but this finding was not significant after adjusting for covariates and multiple comparisons. Among cannabinoid-positive participants, IL-6 levels negatively correlated with PANSS total score ( p  = 0.040), as well as positive ( p  = 0.035) and negative ( p  = 0.024) subscales. Results suggest inflammatory alterations among psychotic individuals with comorbid cannabinoid use.